2005
DOI: 10.1126/science.1117619
|View full text |Cite
|
Sign up to set email alerts
|

The Pseudo-Response Regulator Ppd-H1 Provides Adaptation to Photoperiod in Barley

Abstract: Plants commonly use photoperiod (day length) to control the timing of flowering during the year, and variation in photoperiod response has been selected in many crops to provide adaptation to different environments and farming practices. Positional cloning identified Ppd-H1, the major determinant of barley photoperiod response, as a pseudo-response regulator, a class of genes involved in circadian clock function. Reduced photoperiod responsiveness of the ppd-H1 mutant, which is highly advantageous in spring-so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
892
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 844 publications
(960 citation statements)
references
References 20 publications
39
892
2
2
Order By: Relevance
“…The location and action of this QTL corresponds to Ppd-H1. Indeed, a study by Turner et al (2005) demonstrated that cultivars carrying the dominant Ppd-H1 allele flower 20 days earlier than cultivars carrying the recessive ppd-H1 allele, further supporting our conclusion. This study detected both Ppd-H1 and Ppd-H2 in the 12 h treatment (Table 1).…”
Section: Photoperiod Sensitive Genessupporting
confidence: 78%
See 2 more Smart Citations
“…The location and action of this QTL corresponds to Ppd-H1. Indeed, a study by Turner et al (2005) demonstrated that cultivars carrying the dominant Ppd-H1 allele flower 20 days earlier than cultivars carrying the recessive ppd-H1 allele, further supporting our conclusion. This study detected both Ppd-H1 and Ppd-H2 in the 12 h treatment (Table 1).…”
Section: Photoperiod Sensitive Genessupporting
confidence: 78%
“…Particular photoperiod responsiveness has been selected for in many crops to adapt the plants to specific environments and farming practices (Turner et al 2005). Barley is a long-day photoperiod plant, so that its transition to reproductive growth is significantly delayed when grown under short day conditions (Laurie 1997, Stockinger et al 2007.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3A). In comparison, expression of HvFT, a key gene in the photoperiod response pathway (Turner et al, 2005), was strongly induced by the long-day treatment (Fig. 3B).…”
Section: Resultsmentioning
confidence: 99%
“…In A. thaliana, they appear to influence the time‐keeping mechanism associated with CO transcription in the photoperiodic flowering pathway indirectly through their role in the circadian clock (Nakamichi et al , 2007; Ito et al , 2008). On the other hand, in crops such as barley and rice, their effects on CO transcription are relatively weak, whereas they strongly affect FT transcription (Turner et al , 2005; Campoli et al , 2012; Koo et al , 2013). Therefore, these PRRs are likely to have a more direct effect on the regulation of the photoperiodic flowering pathway.…”
Section: Introductionmentioning
confidence: 99%